First-Principles Study of Alkali and Alkaline Earth Ion Intercalation in Iron Hexacyanoferrate: The Important Role of Ionic Radius - Ling, Chen; Chen, Jiajun; Mizuno, Fuminori (Journal of physical chemistry. C, 2013)
Hexacyanoferrate compounds recently have attracted much interest because of their potential as aqueous and nonaqueous battery cathodes in the application of large-scale energy storage. Here, the feasibility to use iron hexacyanoferrate, Fe[Fe(CN)6], as a cathode candidate for nonaqueous rechargeable batteries is assessed with first-principle calculations. The structural deformation induced by the intercalation of alkali (Li+, Na+, K+, Rb+, Cs+) and alkaline earth (Mg2+, Ca2+, Sr2+, Ba2+) ions into Fe[Fe(CN)6] induces is negligible as compared to other Li-ion battery cathodes. The intercalation is strongly affected by the ionic radius of inserted species. With increasing ionic size, the most stable interstitial site changes from face-centered site to body-centered site. More importantly, the voltages for the intercalation are highly correlated to the ionic radius of the inserted species. The insertion of cations with larger ionic radius happens at higher voltages, and thus provides higher energy density. However, the intercalation of larger cations may also suffer from slower migration kinetics. Thus, it is important to choose inserted cation with appropriate ionic size to achieve the optimized performance. Overall, our results suggest hexacyanoferrate compounds are promising cathode materials for various types of nonaqueous rechargeable batteries.